Religious Identity, Discrimination, and Psychological Distress Among Muslim and Christian Arab Americans - Hashem, Hanan M. (Journal of religion and health, 2021)
This study examines differences in experiences between Muslim and Christian Arabs (N = 1016) utilizing data from the Detroit Arab American Study (DAAS). Results showed that Muslim and Christian Arabs held similar levels of religious centrality and psychological distress but differed in reports of negative religious public regard and experiences of discrimination. Additionally, religious public regard and religious centrality predicted psychological distress similarly for Muslim and Christian Arab Americans. The relationship between religious centrality and psychological distress was mediated by negative religious public regard and perceived discrimination. Study implications are discussed.